Impact of gas flaring on acute respiratory distress among pregnant women and newborn babies in Delta State Central Senatorial District, Nigeria - Omatseye Alero Akuirene; John Esimaje Moyegbone; Charity Omoikhekpen Chukumah; Mercy Ebiyemi Kalaroo; Josiah Obaghwerhievwo Adjene; Emmanuel Agbonomhen Agege; Joseph Onyedenyifa Odoko; Ezekiel Uba Nwose (Journal of Air Pollution and Health, 2024)
Introduction: Gas flaring is a vital environmental issue that has a negative influence on health of population that host natural gases and oil wells. Exacerbated risk of abnormal outcomes for pregnant women and newborn babies are of great concern in maternal and child health. The researchers aimed to examine how gas flaring impact acute Respiratory Distress Syndrome (RDS) in women that were pregnant and newborn babies. Materials and methods: A descriptive cross-sectional survey involving 483 pregnant women of reproductive age, antenatal caregivers and healthcare professionals at health facilities in Delta State Central Senatorial District. Using a multi-stage random sampling technique, a structured survey questionnaire was used to collect respondents’ RDS experiences and that of their new borne. Data were statistically analysed with the use of SPSS. Significant level was considered at P<0.05 Results: Among the 326 children recruited, 205 (42.4%) had experienced respiratory distress. Of the 483 women, 54% suffered from respiratory disease and 33% of the children had been admitted for respiratory distress on a weekly basis. While the age, educational level, gender, and marital status of women were not significant statistically with having children experiencing RDS, bearing children was statistically significant (P<0.001). Health professional reported that developing severe lung infection, release of black carbon and asthma sufferers were major risk factors to RDS. Conclusion: Findings showed that there was an increased prevalence of RDS among the study sub-population. RDS contributes more to cardiovascular disease and diabetes, hence it is important to address this public health issue